PROPERTIES OF COATINGS BASED ON SELF-CROSSLINKING LATEXES CONTAINING NANOPARTICLES OF ZINC OXIDE - Rückerová, Adéla; Machotová, Jana; Puková, Kateřina (CHEMagazín, s.r.o., 2016)
The paper deals with the synthesis and properties of water polymer dispersions. Latexes were prepared by emulsion polymerization with adding zinc oxide during the polymerization in the amount from 0 to 6 wt.%. The paper describes preparation and characterization of latex coatings as well.
Vlastnosti nátěrů na bázi samosíťujících latexů obsahující nanočástice oxidu zinečnatého
Keywords: Latex; zinc oxide; coatings; Latex; oxid zinečnatý; nátěrové hmoty